2021
DOI: 10.1007/s43630-021-00022-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantum energy levels of glutamate modulate neural biophotonic signals

Abstract: Glutamate is the most abundant excitatory neurotransmitter in the brain, and it plays an essential and important role in neural functions. Current studies have shown that glutamate can induce neural biophotonic activity and transmission, which may involve the mechanism of photon quantum brain; however, it is unclear whether such a mechanism follows the principle of quantum mechanics. Here we show that the action of glutamate on its receptors leads to a decrease in its quantum energy levels, and glutamate then … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 41 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Recent research findings have not only verified the feasibility of optical communication in neural circuits but also provided an important basis for establishing a theoretical model of optical communication between nerve fibers ( Kumar et al, 2016 ; Zangari et al, 2018 ; Zarkeshian et al, 2018 ; Ambrosetti et al, 2022 ). Moreover, experimental results have shown that near infrared laser photons induce glutamate release from nerve terminals, and the quantum energy level of glutamate modulate neural biophotonic activity and transmission ( Amaroli et al, 2018 ; Xiang et al, 2020 ; Han et al, 2021 ; Maghoul et al, 2021 ). In the present study, reduced biophotonic activities and spectral blueshift induced by glutamate were found in synaptosomes and brain slices from AD and VaD model animals, indicating that this biophoton imaging technology is accurate and effective in assessing functional changes in synapses and neural circuits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research findings have not only verified the feasibility of optical communication in neural circuits but also provided an important basis for establishing a theoretical model of optical communication between nerve fibers ( Kumar et al, 2016 ; Zangari et al, 2018 ; Zarkeshian et al, 2018 ; Ambrosetti et al, 2022 ). Moreover, experimental results have shown that near infrared laser photons induce glutamate release from nerve terminals, and the quantum energy level of glutamate modulate neural biophotonic activity and transmission ( Amaroli et al, 2018 ; Xiang et al, 2020 ; Han et al, 2021 ; Maghoul et al, 2021 ). In the present study, reduced biophotonic activities and spectral blueshift induced by glutamate were found in synaptosomes and brain slices from AD and VaD model animals, indicating that this biophoton imaging technology is accurate and effective in assessing functional changes in synapses and neural circuits.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis proposed based on early research suggested that biophotons mainly originate from the generation of various reactive oxygen species (ROS) ( Kataoka et al, 2001 ), but our previous results showed that the cytochrome c oxidase inhibitor (sodium azide) did not completely block the biophotonic activities induced by glutamate ( Tang and Dai, 2014b ). Moreover, different quantum levels of glutamate had different effects on biophotonic activities ( Han et al, 2021 ), indicating that the transfer of quantum energy during the process of interactions between active molecules such as neurotransmitters, which serve as biological information mediators, plays an important role in the origin of biophotons. The findings of this study provide direct evidence to confirm that such a quantum biological process not only occurs in synapses, but also undergoes significant changes during the pathological process of AD and VaD animal models, providing new ideas for the development of quantum drug therapies for these diseases.…”
Section: Discussionmentioning
confidence: 99%